A comparative immunohistochemical study of HBsAg, HBcAg and CD57 in chronic hepatitis B pediatric patients with and without malignant disorders - Gülden DİNİZ,; Safiye AKTAŞ,; Ragıp ORTAÇ,; İsmet ÜNLÜ,; Canan VERGİN, (Turkish Journal of Gastroenterology, 2019)
-